2011
DOI: 10.1371/journal.pone.0018928
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Atypical Bacterial Detection in Acute Respiratory Infection in Children Under Five Years

Abstract: BackgroundAcute respiratory infection (ARI) is a leading cause of morbidity and mortality in children worldwide. This study aimed to determine the viral and atypical bacterial causes of different severities and clinical manifestations of ARI in preschool children from low-income families in North-East Brazil.MethodsClinical/demographic data and nasopharyngeal aspirates (NPA) were prospectively collected from children <5 years presenting with ARI over one year to a paediatric A&E department. Disease severity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
150
5
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(203 citation statements)
references
References 32 publications
(44 reference statements)
34
150
5
12
Order By: Relevance
“…Our current study revealed that single rhinovirus (23.0%) and rhinovirus+RSV co-infection (7.6%) were more common in children <2 y. As in our current study, the literature reveals that most rhinoviruses are commonly detected as a single infection (25). The most common co-infections with rhinovirus include the parainfluenza virus and RSV (26).…”
Section: Discussionsupporting
confidence: 78%
“…Our current study revealed that single rhinovirus (23.0%) and rhinovirus+RSV co-infection (7.6%) were more common in children <2 y. As in our current study, the literature reveals that most rhinoviruses are commonly detected as a single infection (25). The most common co-infections with rhinovirus include the parainfluenza virus and RSV (26).…”
Section: Discussionsupporting
confidence: 78%
“…This finding correlates with previous studies that illustrate the common viral-bacterial agents that cause ARI. 7,21,24 Co-infection of influenza A virus and bacterial such as Streptococcus pneumoniae is commonly recognized since secondary infection by Streptococcus pneumoniae were thought to be the cause of death during the 1918 Spanish Flu pandemic. Additionally, secondary bacterial pneumonia and acerbation of underlying conditions during epidemic years are also associate to hospitalization and deaths.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antibiotics is often associated with adverse reactions and community acquired bacterial resistance (Brook, 1998). On the other hand, severe bronchiolitis is commonly associated with bacterial co-infection (Bezerra et al, 2011). For these reasons, it is currently advised that antibiotics are used cautiously when treating bronchiolitis.…”
Section: Antibioticsmentioning
confidence: 99%